An ecological momentary music intervention for the reduction of acute stress in daily life: A mixed methods feasibility study - Feneberg, Anja C.; Nater, Urs M. (Frontiers in Psychology, 2022)
Background: We developed a just-in-time intervention delivering music in moments of stressful experiences in daily life and tested its feasibility using a mixed methods approach. Methods: In this uncontrolled pilot study, the ecological momentary music intervention (EMMI) was tested by ten chronically stressed women aged 23.5±3.3 years. Over 18 consecutive days, whenever participants reported stressful experiences, they were encouraged to listen to a self-compiled playlist. Subjective stress levels and saliva samples were assessed at three time points per stress report. We analyzed app-based log data, in-the-moment responses, questionnaire data, and semi-structured interview data. Results: On average, participants’ compliance with the study protocol lay at 70%. Overall, 65 stressful experiences were reported, 51 of which were followed by music listening, for an average duration of 12:53 minutes. Complete data (i.e., self-reports and saliva samples at all three time points) were provided for 46 stressful experiences. Participants reported immediate relaxation and distraction through music listening. The interviews revealed that the intervention was easy to use and that music listening in moments of perceived stress was viewed as a new and pleasant activity. Several aspects of the protocol (e.g., number of items and prompts) were identified, which will inform adaptations for future studies. Conclusions: Since repeated stressful experiences in daily life can pose a threat to physical and mental integrity, interventions that are easily applicable and deliver support when needed most are necessary. Following minor adaptations, the EMMI can be considered as a feasible approach to target psychobiological stress responses in daily life, which is worthy of investigation in future larger-scale trials.